2022
DOI: 10.3390/biology11020231
|View full text |Cite
|
Sign up to set email alerts
|

5mC-Related lncRNAs as Potential Prognostic Biomarkers in Colon Adenocarcinoma

Abstract: Globally, colon adenocarcinoma (COAD) is one of the most frequent types of malignant tumors. About 40~50% of patients with advanced colon adenocarcinoma die from recurrence and metastasis. Long non-coding RNAs (lncRNAs) and 5-methylcytosine (5mC) regulatory genes have been demonstrated to involve in the progression and prognosis of COAD. The goal of this study was to explore the biological characteristics and potential predictive value of 5mC-related lncRNA signature in COAD. In this research, The Cancer Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…The naturally occurring DNA methylation at the C5 position of cytosine (5-methylcytosine, 5m C) has been demonstrated to function in silencing and activating gene transcription, which could further regulate multiple essential biological processes. , Recently, numerous works have been devoted to elucidating the molecular mechanism of 5m C as an epigenetic mark, enabling significant advances in the development of gene target therapy. , Unfortunately, methylated nucleobases also exhibit poor photostability, leading to the considerable involvement of 5m C in carcinogenesis under ultraviolet (UV) irradiation. , Among all the UV-induced lesions, the most abundant photoproducts are cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6–4) pyrimidines. These lesions are considered to be the main cause of mutations in the genome and may also be precursors for skin cancer. Noticeably, only ∼5% of cytosine is methylated in the human genome, yet 30% of the mutational hotspots that cause skin tumors is linked with those sites. , Accumulating evidence shows that the increased mutagenesis, especially the 5m C → thymine (T) transition, is associated with the formation of CPDs at dipyrimidine sites. , However, current research advances on the mechanism of how methylation regulates the formation of CPD lesions are limited by the lack of knowledge about the photophysical and photochemical properties in 5m C containing DNA systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The naturally occurring DNA methylation at the C5 position of cytosine (5-methylcytosine, 5m C) has been demonstrated to function in silencing and activating gene transcription, which could further regulate multiple essential biological processes. , Recently, numerous works have been devoted to elucidating the molecular mechanism of 5m C as an epigenetic mark, enabling significant advances in the development of gene target therapy. , Unfortunately, methylated nucleobases also exhibit poor photostability, leading to the considerable involvement of 5m C in carcinogenesis under ultraviolet (UV) irradiation. , Among all the UV-induced lesions, the most abundant photoproducts are cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6–4) pyrimidines. These lesions are considered to be the main cause of mutations in the genome and may also be precursors for skin cancer. Noticeably, only ∼5% of cytosine is methylated in the human genome, yet 30% of the mutational hotspots that cause skin tumors is linked with those sites. , Accumulating evidence shows that the increased mutagenesis, especially the 5m C → thymine (T) transition, is associated with the formation of CPDs at dipyrimidine sites. , However, current research advances on the mechanism of how methylation regulates the formation of CPD lesions are limited by the lack of knowledge about the photophysical and photochemical properties in 5m C containing DNA systems.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recently, numerous works have been devoted to elucidating the molecular mechanism of 5m C as an epigenetic mark, enabling significant advances in the development of gene target therapy. 3,4 Unfortunately, methylated nucleobases also exhibit poor photostability, leading to the considerable involvement of 5m C in carcinogenesis under ultraviolet (UV) irradiation. 5,6 Among all the UV-induced lesions, the most abundant photoproducts are cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6−4) pyrimidines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A growing body of research focused on identifying the non-coding lncRNA characteristics to predict survival time and immunotherapy response in COAD patients [20][21][22]. Previous studies suggested that lncRNA, LINC01606, is an oncogene that can promote the stemization and proliferation of tumor cells and inhibit ferroptosis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lncRNAs can in uence the target gene expression through competition with RNAs [19]. Therefore, a growing body of research focuses on identifying the lncRNA characteristics to predict survival time and immunotherapy response in COAD patients [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of biotechnology and the emergence of public databases, bioinformation technology has played an increasingly important role. There have been several previously established lncRNA-based prognostic models for patients with COAD ( Sun et al, 2020 ; Chen et al, 2021 ; Ren et al, 2021 ; Huang et al, 2022 ). This study was the first to establish an m6A-related lncRNA risk model to predict the prognosis, guide immunotherapy, and discover potential chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%